PENGARUH PEMBERIAN PLATELET RICH PLASMA TERHADAP PERBAIKAN SKOR WOMAC DAN GAMBARAN USG LUTUT PADA PASIEN OSTEOARTHRITIS LUTUT DI RSU AL-FAUZAN - Zighri Fahroni Triputro, (2023)
Osteoarthritis affects two out of three elderly people and one out of five young people with an increasing incidence at a young age. The management of OA is based on a combination of pharmacological and nonpharmacological treatments aimed at preventing disease progression. The goals of OA treatment are to relieve pain, improve joint function and cartilage damage, and prevent further cartilage breakdown. Treatments such as analgesics, nonsteroidal and steroidal anti-inflammatory drugs, and corticosteroid injections are sometimes inadequate. Platelet rich plasma is an autologous blood product that contains high levels of growth factors and cytokines that have the potential to alter biological processes involved in the pathogenesis and symptoms of osteoarthritis. A total of sixty patients with knee OA were injected with high or moderate concentrations of PRP. Measurements were measured using the WOMAC questionnaire and ultrasound images of the knee before and after injection. . Data were analyzed using paired T test, unpaired T test, Wilcoxon test and Mann-Whitney test. There was a significant decrease in the WOMAC score (p<0.05) during the post-injection evaluation; there was no significant difference in the improvement of ultrasound knee joint OA during post-injection evaluation (p>0.05)